(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article discusses the use of spoken corpora to enhance language learners’ listening comprehension skills. Spoken corpora provide learners with exposure to authentic spoken language, allowing them to familiarize themselves with natural speech patterns, intonation, and colloquial expressions. Learners can engage in various activities such as transcription, note-taking, and comparative listening to develop their listening accuracy and ability to recognize spoken words and structures. Online platforms and resources like TED Talks, YouTube channels, and linguistic archives such as the International Dialects of English Archive offer valuable spoken corpora for language learners. These resources provide opportunities for listening practice, interactive activities, and targeted learning of specific linguistic features.